Proteção patentária de funcionalidade de software à luz da constituição federal de 1988 - Silva, João Mário Estevam da (2024)
The purpose of this work is to examine the feasibility and dynamics of patenting inventions relevant to software functionalities which consists in a continually evolving area boosted by technological advances. The study highlights the imperative need to safeguard inventiveness since such protection must not infringe competition and free enterprise in order to maintain a harmonious balance between technological innovation and the preservation of the competitive market dynamics. The main hypothesis of this academic work is the possibility in the Brazilian legal order of protecting software functionalities through invention patents. This is because the current prohibition is only related to “computer programs as such” (scientific expression of software), which are already safeguarded by the copyright regime. In this way, the intangibility of the software is explored using the descriptive method and make distinctions between "computer programs", "computer programs as such" and software functionalities to investigate the functionality protection adequacy through patents and their respective analysis criteria. Using the deductive method, I raise documentary, bibliographic, jurisprudential and legislative datas. The choice of this important topic is justified due to the increasing need to protect the legal sphere of the inventor against unauthorized or copying of creations derived from software functionalities. In conclusion, legislative changes to allow the patenting of software functionalities are unnecessary although pertinent. This is because there is no rule in the Brazilian legal order that prevents such protection.